Co-delivery of NIR-II semiconducting polymer and pH-sensitive doxorubicin-conjugated prodrug for photothermal/chemotherapy. (1st January 2022) - Yu, Dongsheng; Wang, Yazhou; Chen, Jifeng; Liu, Shuang; Deng, Shaohui; Liu, Chengbo; McCulloch, Iain; Yue, Wan; Cheng, Du
Abstract: Semiconducting polymer (SP) is a promising photothermal agent in the antitumor application, but the co-delivery of the second near-infrared window (NIR-II)-based SPs with chemotherapeutic drug (e.g., doxorubicin (DOX)) remains a challenge. Here, SPs were firstly improved via backbone and alkyl side-chain engineering, and afterward, SPs and pH-sensitive prodrug copolymer self-assembled into a nanoparticle for a photoacoustic (PA)-imaging guided combination of photothermal therapy and chemotherapy. SP-encapsulated nanoparticles exhibited a high photothermal conversion efficiency of 45% at a relatively low power level of NIR irradiation (0.3 W/cm 2 for 5 min). DOX was rapidly released in response to the acidic lysosomal environment. PA and fluorescence imaging confirmed that the photothermal therapy effectively drove DOX penetration inside tumor tissue, and it resulted in the killing of the surviving tumor cells from hyperthermia. The synergistic effect of SP-based photothermal therapy and DOX-induced chemotherapy was verified in vivo . Overall, the co-delivery of the SP and DOX using pH-sensitive nanoparticles represents a feasible strategy for photothermal therapy with potentially synergistic drug effects. Statement of significance: Recent years have yielded great progress in semiconducting polymers (SPs)-based photothermal therapy for anticancer treatment. However, studies about molecular weight and side-chain of SPs on photothermal conversion efficiency are limited, and investigation of controlled codelivery with chemotherapeutic drug is lacking. Here, we improved the SPs performance via backbone and side-chain engineering, and afterward offered a pH-sensitive DOX-conjugated amphiphilic copolymer to encapsulate SPs. SP-encapsulated nanoparticles exhibited high photothermal conversion efficiency at a clinically feasible power level of NIR irradiation. NIR irradiation-generated hyperthermia not only killed tumor cells but also promoted DOX penetration inside the tumor tissue to ablate the tumor cells that survived hyperthermia. The synergistic effect of SP-based photothermal therapy and DOX-induced chemotherapy was verified in vivo . Graphical abstract: Image, graphical abstract